PENDEKATAN POLITIK PARTI ISLAM SEMALAYSIA (PAS): SATU SOROTAN - Mohd Nasir, Badlisham (Jurnal Syariah, 2019)
PAS's idealism is Islam and struggle to establish an Islamic State. However, establishing an Islamic State is not an easy task and different methods allowed in a democratic country has been adopted so far. This article examined PAS's political mileage right from its establishment until recent years. It also discusses "political compromies" - taJ;aluf siyiisi - that has taken place between PAS and other parties.